SOYA AND ITS ROLE IN CHILDREN’S NUTRITION - T. V. Bushuyeva; T. E. Borovik; T. N. Stepanova; N. N. Semenova (Вопросы современной педиатрии, 2011)
The article presents data on nutritive value of soya as a material for children’s nutrition production. Peculiarities of children’s mixtures based on soy protein isolates for infants’ nutrition and indication for its use are described.